Evaluación Técnico - Financiera de la Tecnología de Conformance Químico en un Campo Petrolero (2018)
This project evaluated the feasibility of bulk gels as a chemical conformance technique in two injection patrons of a Colombian field, there are producing by waterflooding. The conformance technologies look for increase volumetric sweep efficiency during an oil-recovery flood o process being conducted in an oil reservoir. The study cover diagnostic plots, experimental gel evaluation and numerical simulation, to identify a water channer and selection of the patron with major successful probability to implement the technology.